Boosting energy home renovation through innovative business models: ONE-STOP-SHOP solutions assessment. (10th January 2022) - Bagaini, Annamaria; Croci, Edoardo; Molteni, Tania
Abstract: The building sector brings the main responsibility for energy consumption and GHG emissions in European countries. Although many policies have been placed across the EU to increase building energy performance, the current home energy renovation rate remains too low to achieve the EU's decarbonization targets. The One-stop-shop (OSS) concept is emerging as an innovative solution to boost energy home renovation and overcome barriers hindering the renovation process. The OSS is a physical or virtual place where customers obtain multiple products and services at one single point. Through literature review and desk research, 29 OSS initiatives have been analysed in the EU looking at their Business Models (BM). The paper aims to categorize and compare OSS BMs to increase knowledge about OSS functioning and capacity to affect and bring innovation to home renovation process. Three BM archetypes emerge, Facilitation model, Coordination model, and Development model. Within OSS archetypes, seven BM sub-categories have been identified and described. To provide insights for implementing new businesses and revitalizing the home renovation sector, OSS archetypes and sub-categories are compared and assessed, first considering four analytical frameworks and then looking at their capacity to overcome home renovation barriers. Results can be useful to foster energy home renovation by supporting the development of effective and targeted OSS initiatives across the EU. Highlights: One-Stop-Shops play a key role in fostering the energy home renovation process. Several One-Stop-Shops exist in Europe and strongly differ in terms of business model. Three One-Stop-Shop archetypes and seven sub-categories emerged from the analysis. 5 factors shape the models: value proposition, services, revenue, partnership, social value. One-Stop-Shop models lead to different impacts and benefits on the renovation process.